NFR‐aware prioritization of software requirements. Issue 3 (6th April 2021) - Roy, Mandira; Deb, Novarun; Cortesi, Agostino; Chaki, Rituparna; Chaki, Nabendu
Abstract: Non‐functional requirements (NFRs) play a significant role in the software development process. However, the classical requirement prioritization methods for incremental software development, typically, consider the attributes of functional features only, often neglecting the non‐functional constraints. This might lead to catastrophic defects in the system design, as the conflicts among the NFRs are ignored. In this paper, a novel prioritization approach for functional requirements (FRs) is introduced within the incremental software development process. The proposed approach considers the conflicts among NFRs, in the prioritization process, to minimize the incon sistencies of software development. The devised NFR‐aware prioritization algorithm can be tuned according to the weights that the analyst assigns to NFR conflicts and FR‐NFR dependencies. We have assessed our prioritization approach using available requirements data sets and have compared the results in different scenarios.